Trees for a 3-valued logic - Johnson, Fred (Frederick A.), author; Oxford University Press, publisher (Colorado State University. Libraries, 1984)
Johnson claims that Slater is mistaken in identifying his system, presented by using tree rules, with a natural deduction system that results from modifying a system used by Copi. He then modifies Slater's tree rules and shows that these tree rules can be used to pick out precisely those arguments that are valid in a three-valued logic described by Bochvar.
Trees for a three-valued logic
Publisher version: http://www.jstor.org/stable/3327454.
Keywords: logic, symbolic and mathematical; validity; logic; many-valued logics; semantics; trees